Differential of Frequency and Duration Mismatch Negativity and Theta Power Deficits in First-Episode and Chronic Schizophrenia - Xiong, Yan-Bing; Bo, Qi-Jing; Wang, Chang-Ming; Tian, Qing; Liu, Yi; Wang, Chuan-Yue (Frontiers in Behavioral Neuroscience, 2019)
Background: Due to its impairment in patients with schizophrenia, mismatch negativity (MMN) generation has been identified as a potential biomarker for identifying primary impairments in auditory sensory processing. This study aimed to investigate the dysfunctional differences in different MMN deviants and evoked theta power in patients with first-episode schizophrenia (FES) and chronic schizophrenia (CS). Methods: We measured frequency and duration MMN from 40 FES, 40 CS, and 40 healthy controls (HC). Evoked theta power was analyzed by event-related spectral perturbation (ERSP) approaches. Results: Deficits in duration MMN were observed in both FES (p = 0.048, Bonferroni-adjusted) and CS (p < 0.001, Bonferroni-adjusted). However, deficits in frequency MMN were restricted to the CS (p < 0.001, Bonferroni-adjusted). Evoked theta power deficits were observed in both patient groups when compared with the HC (p FES = 0.001, p CS < 0.001, Bonferroni-adjusted), yet no significant differences were found between FES and CS. Frequency MMN was correlated with the MATRICS consensus cognitive battery (MCCB) combined score (r = -0.327, p < 0.05) and MCCB verbal learning (r = -0.328, p < 0.05) in FES. Evoked theta power was correlated with MCCB working memory in both FES (r = 0.347, p < 0.05) and CS (r = 0.408, p < 0.01). Conclusion: These findings suggest that duration MMN and evoked theta power deficits may be more sensitive for detection of schizophrenia during its early stages. Moreover, frequency MMN and theta power could potentially linked to poor cognitive functioning in schizophrenic patients. The findings mentioned above indicated that the neural mechanisms of the three indexes may vary between people.